Science teaching in the upper elementary grades at the Maquiling School a critical study - Bantoc, Margarita (Macalos) 1939- (Quezon City [s.n.], 1971)
A critical study on the science teaching in the upper elementary grades at Maguiling School. This study is concerned with the improvement of the science teaching at Maquiling School.
Thesis (M.A.T. Biology)--University of the Philippines.
Keywords: Science -- Study and teaching (Elementary).; Maquiling School, Inc